Letterature e Migrazioni/Literaturas y migraciones/Littératures et migrations/Literatures and migrations (Altre Modernità, 2009)
Letterature e Migrazioni/Literaturas y migraciones/Littératures et migrations/Literatures and migrationsa cura di/coordinado por/coordonné par/edited by Emilia Perassie/y/et/and Laura Scarabelli